Consensus in first-order nonlinear multi-agent systems with state time delays using adaptive fuzzy wavelet networks. (July 2019) - Taheri, Mehdi; Najafi, Majddedin; Sheikholeslam, Farid; Zekri, Maryam
In this paper, a consensus problem is addressed for first-order multi-agent systems with unknown nonlinear dynamics under undirected graphs. Adaptive fuzzy wavelet networks are used to design two novel control algorithms for nonlinear systems without delays and nonlinear systems with state time delays. In these algorithms, adaptive fuzzy wavelet networks are employed to compensate for nonlinear dynamics of systems. Using proper Lyapunov functions, adaptive laws are obtained and the uniform ultimately bounded stability of closed-loop systems is proved. In addition, this paper uses Lyapunov–Krasovskii functions to handle unknown time delays. Three simulation examples are provided to illustrate the effectiveness of the proposed control schemes.